Semen parameters in men recovered from COVID-19: a systematic review and meta-analysis - Sagar Tiwari (SpringerOpen, 2021)
Abstract Background The novel beta-coronavirus disease (COVID-19) has infected millions of people globally with high risk among males than females. However, the effect of COVID-19 andrology is still a subject of dispute. We planned to analyze the overall consequences of COVID-19 on semen parameters and male sex hormones. Main text Systematic search was performed on MEDLINE and Scopus database until 11 June 2021. We included observational studies, which reported mean ± standard deviation of the semen parameters and serum sex hormones of those reproductive-aged males recovered from COVID-19 and controls who did not suffered from COVID-19. We used Random-effect model to pool the studies, as heterogeneity was present. The Q test and I 2 evaluated heterogeneity. All articles were assessed with their quality and publication bias. We assessed 966 articles for eligibility and found seven eligible studies. These 7 studies included 934 participants with mean age 37.34 ± 10.5 years. Random-effect model meta-analysis showed that men who recovered from COVID-19 had semen parameters less than those who had not suffered from COVID-19. The overall mean difference (MD) [95% confidence interval (CI)] in semen volume, sperm concentration, sperm number, and progressive sperm motility was − 0.20 (− 0.45, 0.05) ml, − 16.59 (− 34.82, 1.65) millions/ml, − 45.44 (− 84.56, − 6.31) millions per ejaculate, − 1.73 (− 8.20, 4.75) percentage respectively. Considering sex hormones, luteinizing hormone and prolactin levels were higher among those recovered with a significant MD (95% CI) of 3.47 (1.59, 5.35)U l−1 and 3.21 (1.71, 4.72)ng ml−1 respectively. Conclusion We found that COVID-19 affects both semen parameters and sexual hormones. However, the mechanism for testicular involvement remains doubtful. Trial registration PROSPERO CRD42021259445